EVALUASI JUMLAH TENAGA KERJA DALAM KONSTRUKSI MENGHADAPI ERA NEW NORMAL - Pratika Riris Putrianti (Prodi Teknik Sipil Fakultas Teknik Universitas Sebelas Maret Surakarta, 2021)
The impact of Covid-19 on the implementation of construction services includes budget cuts, delays in project completion, increased implementation costs, potential for construction disputes. In the era of